2013
DOI: 10.1017/s136898001300116x
|View full text |Cite
|
Sign up to set email alerts
|

Women respondents report higher household food insecurity than do men in similar Canadian households

Abstract: Objective: We investigated factors accounting for the consistently higher levels of household food insecurity reported by women in Canada. Design: Two cycles of the Canadian Community Health Survey for the years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 33 publications
4
80
0
1
Order By: Relevance
“…First, the survey did not record if the person responding to the ELCSA was the same person who provided the blood sample for assessing iron status. This may have not biased the results because ELCSA captures a household level measure although we recognize that previous research indicates that the HFI score may be a function of who is the respondent within the household (40,41). Second, although anemic status was statistically similar between the missing and nonmissing groups, our results may slightly overrepresent women of lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 74%
“…First, the survey did not record if the person responding to the ELCSA was the same person who provided the blood sample for assessing iron status. This may have not biased the results because ELCSA captures a household level measure although we recognize that previous research indicates that the HFI score may be a function of who is the respondent within the household (40,41). Second, although anemic status was statistically similar between the missing and nonmissing groups, our results may slightly overrepresent women of lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 74%
“…Previous research has produced mixed results regarding the role of gender for food security. Studying the off‐reserve population, Matheson and McIntyre () found that women in married households reported higher rates of food insecurity than men, whereas McIntyre, Wu, Fleisch, and Emery () found no difference in the likelihood that female or male respondents would report being food insecure. In our previous analysis with data for Ontario's off‐reserve population, our results indicated that women were less likely to report experiencing less severe levels of food insecurity than men (see Scholz, ) .…”
Section: Resultsmentioning
confidence: 99%
“…They have the desire to protect other family members, especially children, so put themselves at greater risk of food insecurity. As a result, food insecurity may have the most adverse impact on physical and mental health of women (23). Food insecurity can have serious consequences such as stress, anxiety, irritability, social isolation and depression that may leads to lower levels of positive parent-child interactions, and less competent parenting practices (24).…”
Section: Introductionmentioning
confidence: 99%